A hospital-associated measles outbreak in health workers in Beijing: Implications for measles elimination in China, 2018. (January 2019) - Fu, Jiye; Jiang, Chu; Wang, Juguang; Cai, Run; Cheng, Wei; Shi, Lifei; Zhang, Fan; Xu, Zhilan; Xing, Yan
Highlights: We investigated a measles outbreak in health workers in a Chinese medical hospital, Beijing, China. Most cases had no documented measles-containing vaccination before the outbreak. High-level post-exposure measles vaccination contributed largely to contain the outbreak and might provide an indirect protection for inpatients. 2-Dose measles-containing vaccination of susceptible health workers is warranted in China. Abstract: Background: Since the National Action Plan for Measles Elimination 2006–2012 was released in 2006, China has entered into an era of accelerated measles elimination. Despite substantial decline, measles outbreak continued to occur mainly in a non-targeted population, in particular health workers due to occupational exposure. We investigated a measles outbreak in a Chinese medicine hospital, Beijing, in March 2018. Methods: Descriptive analysis was performed on epidemiology of the outbreak, clinical and laboratory evaluations, vaccination status of cases, and public health response. A case-control study was also conducted to identify the associated risk factors for measles. Results: From March 13, 2018, through March 27, 2018, a total of 11 measles cases in health workers were reported in Hospital X, Beijing. The median age of cases was 26 years (range, 21–53) and 4 (36.4%) were male. Of the 11 cases, ten had not been vaccinated or had unknown vaccination status; two occurred in emergency departments. No inpatients became infected, 141 (83.9%) of whom in affected departments were 55 years of age or older. The outbreak was confirmed by laboratory testing; the virus strain was genotype H1. The response activities included isolation of cases, and enhanced health surveillance of health workers and inpatients, particularly in affected departments. A total of 2234 doses of measles-containing vaccines (MCVs) were administered, covering 93.3% of susceptible health workers, in addition to 973 doses to the susceptible individuals in household and community. Lack of documentation of MCV vaccination before the outbreak was identified as a risk factor for measles (odd ratio: 3.333, 95% confidence interval: 1.295–8.621). Conclusions: High coverage of outbreak response immunization activities contributed largely to limit the spread of measles and might provide an indirect protection for inpatients. 2-Dose measles-containing vaccination of personnel in healthcare settings is warranted to prevent potential nosocomial transmission of measles.